Nucleated red blood cell count as a novel predictive biomarker for acute kidney injury and prognosis in patients with acute pancreatitis: A retrospective cohort study - Qiang Yong Yan; Xi Ming Mo; Wen Wu Cai; Yan Peng; Hua Lan Huang (PLoS ONE, 2025)
Objectives Nucleated red blood cells (NRBCs) have been reported to correlate to poor prognosis in critically ill patients. This study aimed to identify the role of NRBC count in early diagnosis of acute kidney injury (AKI) and prediction of poor prognosis in patients with acute pancreatitis (AP). Methods This retrospective cohort study enrolled AP patients who were admitted to our hospital from January 1, 2020 to January 1, 2024. Demographic data, NRBC count, laboratory indicators, and outcomes were recorded. Binary logistic regression analysis was used to identify independent biomarkers for AKI diagnosis and prognosis of AP. Receiver operating characteristic (ROC) curves, net reclassification index (NRI) and integrated discrimination improvement (IDI) were used to evaluate the predictive value of NRBC count. Kaplan-Meier curves were generated to compare survival rate between different groups. Results A total of 486 patients with AP were included in this study. Patients with NRBCs in their peripheral blood were classified into the NRBC (+) group (n = 190), and those without NRBCs in their peripheral blood were classified into the NRBC (-) group (n = 296). Patients in the NRBC (+) group had a higher AKI incidence (29.5% vs 3.0%, p < 0.001) and poor prognosis rate (12.7% vs 1.0%, p < 0.001) than patients in the NRBC (-) group. Binary logistic regression analysis showed that NRBC count was significantly associated with AKI incidence (OR = 3601.361, p < 0.05) and poor prognosis (OR = 204.434, p < 0.05) in AP patients. Area under the ROC curve (AUC) was 0.830 for NRBC count predicting AKI (cutoff value: 0/L) and 0.867 for NRBC count predicting poor prognosis in AP patients (cutoff value: 0.015 × 109/L). Kaplan–Meier survival analysis demonstrated that patients with NRBC count > 0.015 × 109/L (χ² = 85.09, p < 0.001) exhibited significantly lower survival rates during the 30-day follow-up period. NRBC count offered predictive performance comparable to procalcitonin (PCT) and outperformed C-reactive protein (CRP). Conclusion NRBC count serves as a valuable predictive biomarker for both AKI incidence and poor prognosis in patients with AP.